Expansion tube capabilities for studying boost-glide re-entry conditions - Lin, Y; Wallington, JJ; Bui, T; van den Herik, T; James, CM; Chang, EWK; Hermann, TA (Council of European Aerospace Societies, 2024)
The expansion tube is a unique hypersonic impulse facility capable of producing both high-enthalpy and high total pressure conditions simultaneously through the unsteady expansion of a non-stagnated test flow. When coupled with high-performance free-piston or detonation drivers, expansion tubes allow for the simulation of such conditions as scaled Earth re-entry, scaled entry into the atmospheres of other planets in the solar system, and high-speed flight through the Earth’s atmosphere. This paper focuses on the latter case and considers the capabilities of expansion tubes for re-creating the conditions experienced at various parts of the re-entry trajectory of a boost-glide vehicle. Boost-glide vehicles are a type of hypersonic vehicle which is generally boosted just outside the atmosphere by a rocket before ‘gliding’ down through the Earth’s atmosphere to a target, often re-entering at very high-speeds for atmospheric flight of up to Mach 22 (greater than 6 km/s). In a military sense, they are strategically important and are currently being developed by several nations around the world. The expansion tube’s unique ability to simulate high-enthalpy and high total pressure flight makes it particularly well suited to the study of these conditions. This paper will present expansion tube performance envelopes compared to planned boost-glide trajectories, as well as considering specific facility considerations required to generate these conditions.